Proposal To Establish A Resilience and Sustainability Trust. (Policy Papers; Policy Paper, 2022)
The challenges from the pandemic, spillovers from geopolitical shocks, and long-standing structural problems pose an enormous impediment for balance of payments stability and resilient and sustainable growth, especially for low-income and vulnerable middle-income countries. The USD 650 billion SDR allocation in August 2021 has helped support economic stability by supplementing members' reserves. There is scope to amplify the effect of these SDRs by channeling them from countries with strong external positions to countries where the needs are the greatest.